Substance use disorder approaches in US primary care clinics with national reputations as workforce innovators. (23rd August 2021) - O'Malley, Denalee M; Abraham, Cilgy M; Lee, Heather S; Rubinstein, Ellen B; Howard, Jenna; Hudson, Shawna V; Kieber-Emmons, Autumn M; Crabtree, Benjamin F
Abstract: Background: Over the last decade, primary care clinics in the United States have responded both to national policies encouraging clinics to support substance use disorders (SUD) service expansion and to regulations aiming to curb the opioid epidemic. Objective: To characterize approaches to SUD service expansion in primary care clinics with national reputations as workforce innovators. Methods: Comparative case studies were conducted to characterize different approaches among 12 primary care clinics purposively and iteratively recruited from a national registry of workforce innovators. Observational field notes and qualitative interviews from site visits were coded and analysed to identify and characterize clinic attributes. Results: Codes describing clinic SUD expansion approaches emerged from our analysis. Clinics were characterized as: avoidant ( n = 3), contemplative ( n = 5) and responsive ( n = 4). Avoidant clinics were resistant to planning SUD service expansion; had no or few on-site behavioural health staff; and lacked on-site medication treatment (previously termed medication-assisted therapy) waivered providers. Contemplative clinics were planning or had partially implemented SUD services; members expressed uncertainties about expansion; had co-located behavioural healthcare providers, but no on-site medication treatment waivered and prescribing providers. Responsive clinics had fully implemented SUD; members used non-judgmental language about SUD services; had both co-located SUD behavioural health staff trained in SUD service provision and waivered medication treatment physicians and/or a coordinated referral pathway. Conclusions: Efforts to support SUD service expansion should tailor implementation supports based on specific clinic training and capacity building needs. Future work should inform the adaption of evidence-based practices that are responsive to resource constraints to optimize SUD treatment access. Lay Summary: Primary care clinics in the US have been encouraged to expand addiction services to increase treatment access and respond to the opioid epidemic. This study uses structured observations and depth interviews to assess and compare how primary care clinics with innovative workforces have responded to the growing need for substance use disorder treatment. Each of the clinics studied represents a 'case.' We systematically compared cases to understand how and if addiction services were expanded. Twelve clinic 'cases' were coded and characterized based on a continuum of receptivity ranging from avoidant (i.e., resistant), contemplative (i.e., organization members plan to implement change) and responsive (i.e. expansions implemented). Our analysis characterized three clinics as avoidant to expanding addiction services reporting no plans to respond to calls to expand addiction services. Five clinics were characterized as contemplative, meaning they recognized the need but still had reservations and concerns about the expansion. Four clinics were characterized as responsive to addiction service expansion and had several organizational-wide strategies to assess, intervene and treat patients with addictions. Despite national and state-based policies to entice clinics to expand addiction services there was a diversity of approaches observed in clinics. Avoidant and contemplative clinics may need implementation support to build capacity for this type of delivery expansion.